Landscape ethnobotanical study of Malay midwifery plant species: case study of Kelantan - Othman, Rashidi; Khiruddin, Siti ‘Ainmunira (Kulliyah of Architecture and Enviromental Design, International Islamic University Malaysia, 2018)
Traditional Malay midwifery practices in Kelantan exhibit a wide variation in plant materials selection. This study established that plant materials composition selection differs greatly with respect to stage of midwifery practices, locality, environmental factors and culture. A total of 6 types of Malay midwifery practices using plants were observed in 5 different localities in Kelantan. Lenggang perut practice was performed during prenatal treatment whereas another five practices (bertangas, bertungku, berparam, berpilis and mandi serom) were performed during postnatal treatment. In relation to creating Malay garden identity, the findings established that the most influential factor appeared to be a stage of Malay midwifery practices. Each practice has specific purposes and functions which later determine the accumulation of plant materials selection. Of all the Malay midwifery practices studied in this research, we found that mandi serom is the most diverse plant species used which portray the habitat or type of environments in which these plant species origins or found. There may be similarities of some species due to similar knowledge, culture or environment; however, the magnitude of these effects is not as great as plant materials composition selection and usage. By identifying the key factors controlling plant materials selection and usage a greater understanding of how certain midwifery practices influence plant species selection and composition in response to interactions with environmental factors as well as culture, belief and taboos will emerge as potential softscape elements tools and indicator in creating identity of Malay landscape for specific culture and locality.